Volume 5: Turbo Expo 2004, Parts a and B 2004
DOI: 10.1115/gt2004-53774
|View full text |Cite
|
Sign up to set email alerts
|

An Experimental Study on Partial Admission in a Two-Stage Axial Air Test Turbine With Numerical Comparisons

Abstract: This paper presents ongoing experimental aerodynamic and efficiency measurements on a cold flow two-stage axial air test turbine with low reaction steam turbine blades at different degrees of partial admission. The overall objectives of the work are to experimentally investigate and quantify the steady and unsteady aerodynamic losses induced by partial admission. The first results show that both the total-to-static turbine efficiency drops and that the efficiency peak appears at lower isentropic velocity ratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 6 publications
0
8
0
Order By: Relevance
“…The inhomogeneous flow attenuation and structure in 4stage turbine was shown by experimental measure and reported by Bohn [8]. Fridh et al [9] conducted experimental research in partial admission air turbine and the comparison with 2-D compressible model demonstrated the importance of radial components.…”
Section: Introductionmentioning
confidence: 90%
“…The inhomogeneous flow attenuation and structure in 4stage turbine was shown by experimental measure and reported by Bohn [8]. Fridh et al [9] conducted experimental research in partial admission air turbine and the comparison with 2-D compressible model demonstrated the importance of radial components.…”
Section: Introductionmentioning
confidence: 90%
“…Centrifuging of the fluid in the nonadmitted part of the rotor wheel causes an additional form of loss, known as the windage loss. [1][2][3]10,11 Therefore, it is generally known that the efficiency of a partially admitted stage is lower than that of a fully admitted one.…”
Section: Introductionmentioning
confidence: 99%
“…To improve the efficiency of partial admission turbines, several experimental and theoretical studies have been performed to enhance the physical understanding of the nonuniform flow field and the losses involved in the partial admission turbine. 10 Ohlsson 4 addressed the partial admission of an axial flow impulse turbine by a theoretical approach. The results showed that the maximum efficiency of the partial admission turbine occurred at lower velocity ratio.…”
Section: Introductionmentioning
confidence: 99%
“…The rotor passages entering and leaving the jets, originate from flow through certain segments of the first stator rows, would induce additional entropy increases. Fridh et al (2004) experimentally measured the aerodynamic and efficiency of the two stage axial turbine with low reaction steam turbine blades at different partial admission degrees, as well as 2D numerical simulations. The total-to-static turbine efficiency drops and the efficiency peak appears at lower velocity ratios for lower partial admission degrees mostly due to the pumping losses increases with the increased velocity ratios according to their experimental data.…”
Section: Introductionmentioning
confidence: 99%